Espaço e tempo integral na escola: os impasses da formação na sociedade moderna - Lacerda, Lilian dos Santos (2019)
In this study it was investgated how organized school time and space destined to classes of the diversified part of the full-time schools (ETI) curriculum are, in order to verify the existence of possibilities of formative experiences to the students. The adopted procedures for data collection were the observation, through written register and an elaborated script to this means, the use of a questionaire to the ones involved in the educative process (students and teachers) and the analisis of documents and the legislation which guide the ETI Project. The sample of this study was constituted by two state schools located in the municipality of Piracicaba (SP). The theoretical reference adopted to the data analisis was the Critical Theory of Society, specially the contribuitions of Adorno (1966, 1995) and Benjamin (1985, 1985a), with the concept of experience, and of Marcuse (1973) with concepts of technological rationality and the closure of the locution universe. The stablished objective was to analise how the curriculum components of the diversified part classes configurate at the school, in order to understand wether the way how students make use of these spaces and time make formative experiences possible. The main elaborated hypothesis was the one of which the proposal of a full-time school seems to be more of a political tendency that comes from the closure of the political universe promoted by the makers of the educational politics. This situation indicates that the oficial prescriptions may intervene in the thoughts of individuals through means of the ideological use that are made of the discourse and the potentiality of the word, with unfoldings in the development of the critical thinking. When relating the specific objectives with the formulated hypothesis it is possible to assure that the educative process and the formation at the investigated schools occur in a distint way from the proposal of the ETI Project (even with its ideological character), not being possible to perceive elements that point to a teaching concerned with the cultural formation of the students and nothing else beyond the ampliations of the school journey and the ordinary assistance to the students. This is because the education is included at the logical of the advanced capitalism and, this way, it returns the confirmation of the stablished social order, fullfilling the demand of adaptation of the individuals, limiting the possibilities of autonomy, of reflection and criticism of reality